IMPROVING ELEMENTARY SCHOOL STUDENTS’ SELF-CONFIDENCE DURING THE COVID-19 PANDEMIC THROUGH CONCRETE-PICTORIAL-ABSTRACT (CPA) APPROACH IN ONLINE LEARNING - Hafiziani Eka Putri; Erna Suwangsih; Puji Rahayu; Luthfi Aulia Nur Afita; Ni Kadek Yustika Adnyani Dewi; Aan Yuliyanto (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
Covid-19 changes human habits, especially the learning process. Teaching and learning activities that are usually carried out offline now must beconducted online. The research was motivated by the students' assumptions about mathematics which were considered difficult. Students feltoverwhelmed when studying mathematics. When they faced math problems, students often did not have the confidence to solve them. The purpose ofthis study was to determine the increase in the students’ self-confidence through online learning by using CPA approach during the Covid-19pandemic, in terms of overall and Initial Mathematical Ability (IMA). This research was a quasi-experimental research with a non-equivalent controlgroup design on Mathematics subjects on the topic of data collection and presentation at fifth-grade elementary schools. The sample consisted of 56students at one of the elementary schools in Central Jakarta, Indonesia. The research instrument was a self-confidence attitude scale given beforeand after the treatment. The learning process was conducted online through WhatsApp Group, YouTube, and Google Form. The research findingsshowed that CPA approach increased students' self-confidence better than conventional learning, both as a whole and IMA. Thus, CPA approachcould be used as an alternative to increase student self-confidence during the Covid-19 pandemic.